Comparison of the parameters of a flat solar collector with a tubular collector to ensure energy flexibility in smart buildings - Kunelbayev, Murat; Mansurova, Madina; Tyulepberdinova, Gulnur; Sarsembayeva, Talshyn; Issabayeva, Sulu; Issabayeva, Darazha (International Journal of Innovative Research and Scientific Studies, 2024)
This study examines the application and implementation of energy-efficient measures and strategies for use in buildings aimed at achieving the goal of virtually zero energy consumption by buildings. In particular, the aim of the study is to introduce integrated solar devices into the building, functioning as a functional component of the structure for heat storage, in order to increase the flexibility of the structure while maintaining comfortable conditions inside. This article discusses an experimental comparison of flat and tubular solar collectors in the southern and northern regions of Kazakhstan. Compared to glass (S = 3), a tubular solar collector has a coefficient of thermal conductivity that is two times lower for single-layer elements and 2.5 times lower for double-layer elements. This means that less heat is lost. A flat solar collector was also developed, a heat-insulating translucent double-glazed window with reduced pressure, and the coolant is made of thin-walled corrugated stainless-steel pipe. In this collector, there is a constant circulation of heat, which increases the efficiency of heat transfer by eliminating additional partitions between the panel and thermal insulation. A calculation was carried out that allowed us to determine the productivity and useful gain for two collectors. The annual increase in the useful energy of flat solar collectors is about 12780000 kJ/hour and 20100000 kJ/hour for tubular solar collectors; therefore, the annual increase in the useful energy of evacuated tubular collectors is 20% more than that of flat plate collectors in the northern region.